2015
DOI: 10.1371/journal.pone.0143306
|View full text |Cite
|
Sign up to set email alerts
|

Co-Inhibition of GLUT-1 Expression and the PI3K/Akt Signaling Pathway to Enhance the Radiosensitivity of Laryngeal Carcinoma Xenografts In Vivo

Abstract: In the present study, we investigated the role of GLUT-1 and PI3K/Akt signaling in radioresistance of laryngeal carcinoma xenografts. Volume, weight, radiosensitization, and the rate of inhibition of tumor growth in the xenografts were evaluated in different groups. Apoptosis was evaluated by TUNEL assay. In addition, mRNA and protein levels of GLUT-1, p-Akt, and PI3K in the xenografts were measured. Treatment with LY294002, wortmannin, wortmannin plus GLUT-1 AS-ODN, and LY294002 plus GLUT-1 AS-ODN after X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 35 publications
4
41
1
Order By: Relevance
“…Glut-1 also affects cell proliferation and chemoradiotherapy sensitivity of head and neck squamous cell carcinoma, including laryngeal carcinoma13-18. Our previous studies suggested that Glut-1 may affect the proliferation, glucose uptake, chemosensitivity, and radiosensitivity [8,[13][14][15][16][17]. Although we found that the mechanism may be mediated through the PI3K/Akt pathway, the role of the activated PI3K/Akt pathway in this process was not significant.…”
Section: Introductioncontrasting
confidence: 72%
“…Glut-1 also affects cell proliferation and chemoradiotherapy sensitivity of head and neck squamous cell carcinoma, including laryngeal carcinoma13-18. Our previous studies suggested that Glut-1 may affect the proliferation, glucose uptake, chemosensitivity, and radiosensitivity [8,[13][14][15][16][17]. Although we found that the mechanism may be mediated through the PI3K/Akt pathway, the role of the activated PI3K/Akt pathway in this process was not significant.…”
Section: Introductioncontrasting
confidence: 72%
“…Especially in HNSCC, the AKT signal transduction pathway is involved in the most important mechanisms of radioresistance: intrinsic radioresistance, tumor-cell proliferation, and hypoxia (3). Several studies have showed that suppressing AKT activity sensitizes cancer cells to irradiation (34)(35)(36). Therefore, our study provided evidence that TSA induced apoptosis in TSCC cells by upregulating miR-375 and subsequently suppressing the AKT cascade.…”
Section: Discussionsupporting
confidence: 51%
“…Glucose is the main energy source for tumor cells and GLUT-1 is a key transporter of extracellular glucose [6,7,29]. GLUT-1 is overexpressed in many cancers, including laryngeal carcinoma, and is associated with their metastasis, drug resistance, and prognosis [6,7,[30][31][32][33][34][35][36]. We investigated the role of GLUT-1 in Tu212…”
Section: Discussionmentioning
confidence: 99%